Studi Komparasi Dan Analisis Terhadap Tindak Pidana Kesusilaan Zina, Pemerkosaan Dan LGBT Dalam Perspektif KUHP Dan RKUHP 2015 - Hj. Khusnul Hitaminah; Muhammad Zainal (JUSTNESS - Jurnal Hukun dan Agama, 2021)
The law as we know it has three concepts that are the essence and foundation of the law itself, namely providing justice, providing benefits and certainty. Law is born, grows and develops with the community, meaning that the law undergoes a process of change at any time along with the development of people's behavior, therefore the law must be dynamic so that people are protected and their safety is guaranteed when they feel their life is threatened. One of the things that is rife in society lately is the occurrence of sexual harassment, rape and free same-sex sexual relations, all of which are troubling to us as a nation that has high civilization by upholding moral values, but it is tarnished by the rise of incidents such as illustrated above. Therefore, the law has an active role as a tool to protect and prevent that what has been described above is an extraordinary event in our country. So that peace, peace and the image inherent in our nation that upholds the honor of moral values can be guaranteed for its sustainability. Along with that, although all this research is normative, it aims to provide information to the public that the law must be dynamic and not stagnant considering that society is always dynamic along with the times, so that this research conducts a study and comparative study of the laws that apply now and in the future, which of course this is a form or manifestation of our concern and the state apparatus to ensure the safety and comfort of the community. From some of these explanations, the author takes the title "Comparative Study and Analysis of Crimes of Morality, Adultery, Rape and LGBT in the Perspective of the 2015 Criminal Code and RKUHP" with the following objectives: For the public in general, to know that the articles in the Criminal Code that regulate the issue of adultery, rape and LGBT are too specific and narrow so they need to be expanded to be more comprehensive. To let the public know that the legislative body has tried to make new breakthroughs by adding new articles in the Criminal Code regarding the rules regarding Adultery, Rape and LGBT. With the addition of articles in the new Draft Criminal Code, it is possible to contribute justice to all victims of adultery by means of violence or rape. It is also hoped that with this RKUHP people will no longer have same-sex intercourse, which is carried out freely without any sanctions for the perpetrators.. Keyword: Comparative Study, Moral Crimes, Criminal Code and RKUHP